Effect of dexamethasone gargle, intravenous dexamethasone, and their combination on postoperative sore throat: a randomized controlled trial - Seunghee Ki; Inwook Myoung; Soonho Cheong; Sehun Lim; Kwangrae Cho; Myoung-hun Kim; Yongjae Han; Minkyung Oh; Yohan Park; Kwanghee Kim; Jeonghan Lee (Anesthesia and Pain Medicine, 2020)
Background Postoperative sore throat (POST) is a complication that decreases patient satisfaction and increases postoperative complaints. The present study was conducted to investigate effects of gargling with dexamethasone, intravenous dexamethasone injection and the combination of the two on the incidence and severity of POST. Methods Study participants were 96 patients who had undergone laparoscopic cholecystectomy, randomly allocated into three groups. Group G gargled with 0.05% dexamethasone solution and were infused intravenous 0.9% normal saline before general anesthesia; group I gargled with 0.9% normal saline and were infused intravenous 0.1 mg/kg dexamethasone; group GI gargled with 0.05% dexamethasone solution and were infused intravenous 0.1 mg/kg dexamethasone. The incidence and severity of POST, hoarseness and cough were evaluated and recorded at 1, 6, and 24 h after the surgery. Results There were no significant differences in the total incidence of POST up to 24 postoperative hours among Group G, Group I and Group GI (P = 0.367, Group G incidence = 34.38%, [95% confidence interval, 95% CI = 17.92–50.83], Group I incidence = 18.75%, [95% CI = 5.23–32.27], Group GI incidence = 28.13%, [95% CI = 12.55–43.70]). The other outcomes were comparable among the groups. Conclusions In patients who had undergone laparoscopic cholecystectomy, gargling with 0.05% dexamethasone solution demonstrated the same POST prevention effect as intravenous injection of 0.1 mg/kg dexamethasone. The incidence and severity of POST were not significantly different between the combination of gargling with 0.05% dexamethasone solution and intravenous injection of 0.1 mg/kg dexamethasone and use of each of the preventive methods alone.